DOCTORS’ POSTGRADUATE EDUCATION: CLINIC-PHARMACEUTICAL TRAINING - Tsekhmister, Yaroslav; Lysenko, Oleksandra (Continuing Professional Education: Theory and Practice, 2019)
The proposed article presents the key features of modern pharmaceutical assistance to the population; highlights the differences between the concepts «clinical pharmacy»and «clinical pharmacology»; describes the place of clinical pharmacy in the implementation of programs of pharmaceutical care aimed at preventing undesirable effects associated with the use of drugs; substantiates the expediency of clinical pharmacy programs introduction to the doctors’ postgraduate education course; substantiates the expediency of introduction of a practical course on clinical pharmacy for medical interns; describes the main idea of the clinical pharmacy practical course as a modelling of the real clinical situation which requires the adequate medical support selection leaning on the basis of previous knowledge on pharmacokinetics, drug interaction, adverse reactions and also pharmacoeconomics;suggests the proposal for the definition of a World Health Organization Model List of Essential Medicine, as well as clinical protocols of medical care developed on the principles of evidence-based medicine as a basis for practical training in clinical pharmacy; determines the priority of applying the case-method, as well as the method of four steps in arranging classes in clinical pharmacy as suchwhich corresponds most closely to the training objectives of the course and the needs of adult learners.